2019
DOI: 10.1080/02670836.2018.1563982
|View full text |Cite
|
Sign up to set email alerts
|

On the statistical distribution of primary and secondary dendrite arm spacing in cast metals

Abstract: Statistical distributions of dendrite arm spacing have not been addressed in the literature. Two histograms for primary dendrite arm spacing in a cast nickel-based superalloy, and four histograms from a chill cast 5182 aluminium alloy ingots for secondary dendrite arm spacing have been analysed. For all datasets, lognormal distribution provided excellent fits to the data. Moreover, the Lifshitz–Slyozov–Wagner distribution was found to have systematic error in the fits to the secondary arm spacing data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In the literature, a significant amount of steady state solidification work is reported that characterises the relationship between primary spacing, alloy composition, C 0 , thermal gradient, G, and tip growth velocity, V [33][34][35][36][37][38][39][40][41]. In directional solidification, the G and V can be independently controlled, so one may study the dependence of λ 1 , on either G (at constant V) or V (at constant G).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, a significant amount of steady state solidification work is reported that characterises the relationship between primary spacing, alloy composition, C 0 , thermal gradient, G, and tip growth velocity, V [33][34][35][36][37][38][39][40][41]. In directional solidification, the G and V can be independently controlled, so one may study the dependence of λ 1 , on either G (at constant V) or V (at constant G).…”
Section: Introductionmentioning
confidence: 99%
“…Regrettably, these structures often prove resilient even when subjected to thermal-mechanical treatments such as forging, rolling, and heat treatment. Consequently, a well-established body of research exists dedicated to exploring the relationship between dendritic structures and the properties of materials [1][2][3][4][5][6][7][8][9][10][11]. Secondary dendrite arm spacing (SDAS, λ 2 ) is commonly used to observe casting and the ensuing manufacturing processes, primarily due to its significant influence on the mechanical and magnetic characteristics of magnetic alloys [3].…”
Section: Introductionmentioning
confidence: 99%
“…For example, alloy or trace element adding can reduce the size of SDAS [1,2]; local solidification time is crucial for the cooling rates and affects the SDAS size and distribution of casting alloys [5]. Besides, many methods have been investigated to reasonably determine the SDAS and its relation to the properties of materials [8,10,11]. Concurrently, SDAS is intricately associated with the solidification mechanisms [3,4], growth patterns [7,9], and distribution of solute, inclusions, and interfacial phases within the material matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Classical methods to determine the average [ 11 , 12 , 13 ] and local [ 14 , 15 , 16 , 17 , 18 , 19 ] PDAS, all require laborious manual determination of the dendrite cores. The manual counting process takes approximately 20 min to 1.5 h depending on the size of the sample surface and number of dendrites.…”
Section: Introductionmentioning
confidence: 99%